2011
DOI: 10.1681/asn.2010090987
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin in Diabetic Hemodialysis Patients

Abstract: A randomized, placebo-controlled trial in diabetic patients receiving hemodialysis showed no effect of atorvastatin on a composite cardiovascular endpoint, but analysis of the component cardiac endpoints suggested that atorvastatin may significantly reduce risk. Because the AURORA (A Study to Evaluate the Use of Rosuvastatin in Subjects on Regular Hemodialysis: An Assessment of Survival and Cardiovascular Events) trial included patients with and without diabetes, we conducted a post hoc analysis to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 43 publications
0
50
0
Order By: Relevance
“…Authors suggested several possibilities contributing to these findings which include exclusion of patients < 50 years of age and those who have been on statin, high percentage of patients leaving the study, and lower than expected yearly cardiovascular event rates. In post hoc analysis of this trial among diabetics (n = 731), rosuvastatin did not have significant effect on primary end-point although rosuvastatin group had significant decrease in cardiovascular events (HR = 0.68, 95%CI: 0.51-0.90) [55] . SHARP trial [35] included CKD patients on dialysis as well as not on dialysis.…”
Section: Recommendations For Usementioning
confidence: 76%
“…Authors suggested several possibilities contributing to these findings which include exclusion of patients < 50 years of age and those who have been on statin, high percentage of patients leaving the study, and lower than expected yearly cardiovascular event rates. In post hoc analysis of this trial among diabetics (n = 731), rosuvastatin did not have significant effect on primary end-point although rosuvastatin group had significant decrease in cardiovascular events (HR = 0.68, 95%CI: 0.51-0.90) [55] . SHARP trial [35] included CKD patients on dialysis as well as not on dialysis.…”
Section: Recommendations For Usementioning
confidence: 76%
“…Rosuvastatin significantly reduced the LDL-C levels, but it was not able to inhibit cardiovascular events [85]. However, a sub-analysis of the AURORA trial demonstrated that rosuvastatin reduced cardiovascular events (32 % reduction compared to control) in patients with diabetes on hemodialysis [86]. On the other hand, statin therapy failed to show secondary prevention of cardiovascular events in the Swedish Web-system for Enhancement and Development of Evidence-based care in Heart disease Evaluated According to Recommended Therapies (SWEDEHEART) study [87].…”
Section: End-stage Renal Failure and Lipid-lowering Therapymentioning
confidence: 99%
“…These results differ from two other placebo-controlled statin trials in dialysis populations that did not demonstrate a reduction in cardiovascular death, MI and stroke, 89,90 although secondary analyses from the AURORA study suggest some benefit from rosuvastatin treatment in dialysis patients with diabetes. 91 This failure to achieve statistical significance in primary trials may have derived from the smaller number of participants enrolled in these trials. The SHARP study also noted that statin therapy was safe in patients with kidney disease.…”
Section: Statinsmentioning
confidence: 99%